Digitalization of MSME Accounting in Meeting Recording Standards Based on SAK EMKM in Putra Mandiri Transportation Services With The Akuntansiku Application - Novi Rahmawati; Muhammad Syahbudi; Rahmat Daim Harahap (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Finance is crucial in a business, so the preparation of financial reports according to standards needs to be done in order to know the condition of the business and business finances. This study was conducted to determine the application of digitalization of MSME financial reports and the conformity of recording based on SAK EMKM. The study was conducted using a qualitative method by implementing the Akuntansiku application and the conformity of the application with SAK EMKM carried out at the Putra Mandiri Transportation Service Business which had not implemented financial recording according to standards. The results of the study stated that the application of financial report preparation with the Akuntansiku Application presented a Financial Position Report in 2024 which presented Assets of Rp. 1,087,991,000; Liabilities of Rp. 108,870,000; and Equity of Rp. 979,121,000. The 2024 Profit and Loss Report which presented business income and other income of Rp. 663,955,000; expenses and other expenses of Rp. 310,478,000; and obtained a net profit of Rp. 71,537,000. The implementation of the Akuntansiku Application is suitable for use by Putra Mandiri businesses and other MSME actors because it has complied with the EMKM SAK